Y-Configuration Stent Placement (Crossing and Kissing) for Endovascular Treatment of Wide-Neck Cerebral Aneurysms Located at 4 Different Bifurcation Sites - Zhao, K.-J. (AJNR Am J Neuroradiol, 2012)
BACKGROUND AND PURPOSE: The Y-stent technique, including crossing-Y and kissing-Y, is a promising therapeutic option for some complex bifurcation aneurysms. Here, its efficacy and safety are evaluated on the basis of 11 bifurcation aneurysms. MATERIALS AND METHODS: A retrospective review was conducted for all patients who underwent endovascular treatment of aneurysms in our department between January 2009 and June 2011 to identify and analyze cases with bifurcation aneurysms reconstructed by using Y-stents. RESULTS: Eleven patients (4 ruptured and 7 unruptured aneurysms) were identified (4 men, 7 women) with a mean age of 60.4 years. Nine aneurysms (2 AcomAs, 3 MCA-Bifs, 1 PcomA, 3 BA apexes) were treated by using the crossing-Y technique, and 2 (both BA apexes) were treated with the kissing-Y technique, achieving complete occlusion in 6 aneurysms, residual neck in 4, and partial occlusion in 1. Perioperatively, a single thromboembolic event occurred in 1 case without neurologic deficit, which required a salvaging second stent implantation. Means of 9.9 months of angiographic and 13.7 months of clinical follow-up were available. As a result, 9 (81.8) aneurysms were completely occluded, 1 with a residual neck remained stable, and 1 residual aneurysm sac was recanalized, which was retreated and achieved a complete occlusion. All patients were independent with an mRS score of 0–1 at discharge and follow-up. CONCLUSIONS: In selected patients, the reconstruction of bifurcation aneurysms by using the Y-stent can be successfully achieved with satisfactory midterm results.